Adaptation of durum wheat to a changing environment - Cattivelli L.; Miglietta F.; Zaldei A.; Rizza F.; Mastrangelo A.M.; De Vita P.; Mazzucotelli E. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
The expected climatic changes will lead to an environment characterized by elevated atmospheric CO2, increased temperatures and increased risks for drought due to an elevated atmospheric evaporative demand. Therefore the traits involved in the adaptation to abiotic stresses, particularly drought and heat, as well the capability of the plants to adjust their metabolism to the increased CO2 concentration will play a key role to sustain yield (and yield quality) in the durum wheat crop in the next years. This report summarizes a number of studies dedicated to the understanding the physiological and molecular basis of durum wheat adaptation to environmental stress. The overall findings highlight the existence of a significant degree of genetic variation that will allow the selection of new cultivars with a specific adaptation mechanism for the new or changed climatic conditions.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)